Real options for determining optimum time systems sylvopastoral: investment analysis - Milanesi, Gastón; Broz, Diego Ricardo; Woitschachz, Guillermo Bruno (Instituto de Ecología, A.C., 2013)
In this work we assess, from an economic and financial perspective, the optimal time of timberharvest in joint forestry-pasture systems. For this we apply a Real Options (RO) approach as a tool ofstrategic decision making. It assumes a stochastic process of price projections and is compared with thepresent value (NPV) computed on the basis of a fixed rate all along the project. The results obtained bymeans of the RO approach recommend cutting at 18 years with a ROV (Real Options Valuation) of $AR1 088 339 (ARG) against the alternative NPV assessment that recommends cutting at 11 years andyields $AR 511 914.